Peculiarities in the reconstruction of dehydrated and rehydrated Tutoplast transplants - Dedukh, Ninel (ORTHOPAEDICS TRAUMATOLOGY and PROSTHETICS, 2009)
An experimental-morphological study of spongy dehydrated and rehydrated Tutoplast specimens, transplanted to a modelled defect of the femoral bone in 18 rats, was made. It was shown that a preliminary rehydration of Tutoplast transplants produced an optimizing effect on their reconstruction and osteorepair in the bone defect.